Case Report: An Adolescent Girl with Isolated Neuropsychiatric Features and Apparent Post-Malaria Neurological Syndrome - Panda, Prateek Kumar (Am J Trop Med Hyg, 2020)
The post-malaria neurological syndrome (PMNS) is an unusual and relatively underreported complication of malaria, which usually occurs after the resolution of acute febrile illness and the patient is free from parasitemia. The clinical spectrum of the PMNS varies from acute-onset cerebellar ataxia to significant encephalopathy with focal deficits resembling acute disseminated encephalomyelitis. Uncommon presentations of PMNS include Guillain–Barre syndrome, postural tremor, or even isolated neuropsychiatric features. Although in a significant proportion of PMNS cases clinical resolution occurs with conservative treatment only, corticosteroids have been used in an attempt to hasten recoveries. Here, we present a case of a 12-year-old girl with acute onset, isolated neuropsychiatric features, following Plasmodium falciparum malaria. Neuroimaging, clinical examination, and cerebrospinal fluid studies were within normal limits. The child recovered completely after treatment with methylprednisolone pulse therapy. This case report illustrates the need for creating awareness about this uncommon complication of malaria. In view of the uncommon complication, early diagnosis and prompt treatment might help in the early resolution of symptoms.